A Cu-Cr-Zr alloy for high current electrical connector and preparation method thereof

Through the molding deformation, cold rolling and combined heat treatment of Cu-Cr-Zr alloy, combined with the addition and aging treatment of Cr, Zr, Ge and Nb elements, the contradiction between strength and conductivity of copper alloy materials is solved, and the High strength, high conductivity and good high temperature resistance to meet the application needs of high-current electrical connectors.

CN116179887BActive Publication Date: 2025-01-10FUZHOU UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310217588.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2025-01-10
Estimated Expiration
2043-03-08

AI Technical Summary

Technical Problem

Existing copper alloy materials are difficult to maintain high conductivity while increasing strength, and higher strength, hardness and high-temperature softening properties are required in high-current electrical connector applications to meet the needs of miniaturization, thinning and high-temperature environments.

Method used

Cu-Cr-Zr alloy is used to add Cr, Zr, Ge and Nb elements through molding deformation, cold rolling and combined heat treatment processes to form a variety of precipitation phases to improve hardness and conductivity, and combine stage aging and room temperature rolling. The process reduces internal stress and optimizes microstructure.

Benefits of technology

The high hardness, strength, high temperature softening resistance and high conductivity of Cu-Cr-Zr alloy are achieved, meeting the comprehensive performance requirements of high-current electrical connectors, and significantly improving the mechanical properties and conductivity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116179887B_ABST
    Figure CN116179887B_ABST
Patent Text Reader

Abstract

The present invention discloses a Cu‑Cr‑Zr alloy for a high-current electrical connector and a preparation method thereof. The copper alloy material is composed of the following components: 0.80-1.20wt% Cr, 0.10-0.30wt% Zr, 0.10-0.30wt% Ge, 0.01-0.06wt% Nb, and the rest is Cu. Its preparation method comprises the steps of alloy casting, homogenization treatment, hot rolling, solution treatment, die deformation, stage aging treatment, room temperature rolling and variable temperature aging treatment. The copper alloy material obtained by the present invention has fine grains and forms fine, dispersedly distributed precipitation phase particles, so as to have good comprehensive properties such as hardness, strength, high temperature softening resistance and electrical conductivity, and can be widely used in related fields such as electronic power, especially electrical connectors that need to work in a high current environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloy materials, and in particular relates to a method for preparing a copper alloy by combining die pressing, cold rolling and combined heat treatment. Background Art

[0002] Copper and copper alloys are widely used in many fields such as electronic power, rail transportation, national defense and military industry due to their good electrical conductivity, thermal conductivity and mechanical properties. These applications are closely related to our daily life and are the basis for the healthy development of the national economy. Pure copper has excellent electrical conductivity and thermal conductivity, but the low strength of pure copper (the tensile strength of industrial pure copper is only about 230MPa) greatly limits the scope of use of pure copper. For copper alloys, high strength and high conductivity are a pair of contradictory properties. How to effectively improve the strength of copper alloy materials while maintaining their high conductivity has become a research hotspot for high-strength and high-conductivity copper alloys. At present, people usually improve the strength of copper alloys by alloying and changing their processing technology, while ensuring the high conductivity of copper alloys.

[0003] Current copper alloy strengthening methods include solid solution strengthening and precipitation strengthening. For solid solution strengthened copper alloys, alloying elements are dissolved in the copper matrix, resulting in lattice distortion of the copper matrix. While the strength of the alloy is limited, the probability of electron scattering is increased, thereby reducing its conductivity. For example, the Cu-Sn-Ti-P-Zn-Mg alloy prepared in the Chinese patent "A method for preparing a high-performance copper alloy" (authorization announcement number: CN109266877B) has a hardness of 225HV and a tensile strength of 720MPa, but its conductivity is only 12.6%IACS. For precipitation-strengthened copper alloys, the copper alloy in the supersaturated solid solution state is cold deformed to increase the density of microscopic defects such as dislocations and vacancies, and then combined with an aging heat treatment process, the solute atoms dissolved in the copper matrix nucleate and precipitate from the microscopic defects during the heat treatment process to form fine and dispersed precipitation phase particles, which plays a precipitation strengthening role. The precipitation of solute atoms can reduce the lattice distortion of the copper matrix, reduce the probability of electron scattering, and improve the conductivity of the alloy. For example, Liu Haibin et al., "Effects of rolling and aging treatment on the structure and properties of Cu-Cr-Zr alloy", Journal of the Chinese Society of Nonferrous Metals, 2020, 30(9):9, the strength of the prepared Cu-Cr-Zr alloy is 411.7MPa and the conductivity is 63.7%IACS. Its strength and conductivity cannot fully meet the performance requirements of high-current electrical connectors.

[0004] With the advent of the 5G era, various electrical connectors such as new energy vehicle connectors, aerospace connectors, and new generation intelligent terminal high-speed transmission standardized ports are developing in the direction of miniaturization, thinness, high density, and long life. This puts forward higher requirements for various electrical connectors (especially high-current power connectors), such as: greater working current density, better high temperature resistance, higher reliability, and good plug resistance. On the one hand, due to miniaturization, the materials used become thinner. In order to ensure the reliability of the connection and prevent plastic deformation during the plug-in process, the materials used must have higher strength and hardness. On the other hand, in order to adapt to high current working scenarios and prevent the failure of the electrical connector due to excessive heat generation during current transmission, the materials used need higher conductivity and higher softening resistance. The present invention improves the composition and innovates the process on the basis of the Cu-Cr-Zr ternary alloy. By combining mold deformation, cold rolling and combined heat treatment, the copper alloy has high hardness, high strength, good high temperature softening resistance and high conductivity and other comprehensive properties at the same time to meet the performance requirements of high current electrical connectors. Summary of the invention

[0005] The object of the present invention is to provide a Cu-Cr-Zr alloy for high-current electrical connectors and a preparation method thereof. The copper alloy has good comprehensive properties such as high hardness, high strength, good high-temperature softening resistance and high conductivity, and can be widely used in related fields such as electronics and electricity, especially electrical connectors that need to work in high-current environments.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A Cu-Cr-Zr alloy for a high-current electrical connector comprises the following components: 0.80-1.20wt% of Cr, 0.10-0.30wt% of Zr, 0.10-0.30wt% of Ge, 0.01-0.06wt% of Nb, and the remainder of Cu, with the sum of the mass percentages being 100%.

[0008] Furthermore, the sum of the mass percentages of Cr+Zr is 0.90~1.50wt%, and the sum of the mass percentages of Ge+Nb is 0.11~0.36wt%.

[0009] The present invention provides a method for preparing a Cu-Cr-Zr alloy for a high-current electrical connector, comprising the following steps:

[0010] (1) Alloy casting: Under the protection of pure argon (Ar volume fraction ≥ 99.99%), the raw materials are placed in an induction furnace for smelting, and then the resulting alloy melt is heated to above 1200°C, allowed to stand for 10 minutes, then cast into a mold and cooled to room temperature to obtain an alloy ingot. The raw materials used are pure copper blocks with a purity of ≥ 99.9wt%, containing 5~10wt% of Cu-Cr master alloy, 40~60wt% of Cu-Zr master alloy, 10%~20wt% of Cu-Ge master alloy, and 0.5~1.0wt% of Cu-Nb master alloy;

[0011] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C to 980°C for 5 to 8 hours, and then cooled to room temperature with the furnace;

[0012] (3) Hot rolling: The homogenized alloy material is heated to 700℃~850℃ and kept at this temperature for 5~10 minutes, then taken out and quickly hot-rolled into a strip. The total deformation of hot rolling is 60%~85%. The hot-rolled alloy strip is immediately water quenched and quickly cooled to room temperature.

[0013] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 900°C to 1050°C for 30 to 60 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0014] (5) Compression molding: Remove the surface oxide scale of the alloy strip after solid solution treatment, and then perform compression molding at room temperature for 8 to 20 times. The compression molding die includes a groove die (tooth die) and a flattening die. The upper die of the groove die (tooth die) is provided with a groove, and the lower die is provided with a convex tooth. The convex tooth and the groove can be engaged with each other. The groove height and groove width of the upper die groove and the tooth height and tooth width of the lower die convex tooth are equal, which is 3 to 10 mm, and are distributed at equal intervals. The compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the slot die, and interlocking the upper die groove with the lower die convex teeth to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the slot die, and moving its placement position by an odd number of tooth widths along the lateral direction of the convex teeth relative to the last placement position, and then compression molding the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④. Among them, one compression molding consists of a complete implementation of steps ①②③④;

[0015] (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 200-250°C at a rate of 5-15°C / min and kept at this temperature for 30-60 minutes; then, the temperature is raised to 400-460°C at a rate of 5-15°C / min and kept at this temperature for 90-120 minutes; then, the temperature is lowered to 150-250°C at a rate of 5-15°C / min and kept at this temperature for 30-60 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0016] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 50%~90%;

[0017] (8) Temperature aging treatment: The alloy strip rolled at room temperature is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 300-350°C at a rate of 5-15°C / min and kept at this temperature for 1-2 minutes; then, the temperature is raised to 400-500°C at a rate of 5-15°C / min and kept at this temperature for 15-30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample.

[0018] The advantages of the present invention are

[0019] (1) The present invention uses Cu, Cr, Zr, Ge, and Nb as the main elements in the alloy composition. The composite addition of Cr, Zr, Ge, and Nb elements in the alloy composition can effectively reduce the stacking fault energy in the copper matrix, inhibit the cross-slip and climb of dislocations, and help to form more microscopic defects such as twins and stacking faults during mold deformation and cold deformation, and refine the cold deformation structure, providing more precipitation phase nucleation sites, thereby improving its hardness, strength, and high temperature softening resistance. In addition, according to the Miedema mixing enthalpy theory, the mixing enthalpy between Ge-Nb and Ge-Zr is greater than that between Cu-Zr, Cu-Ge, and Cu-Nb. Therefore, the copper alloy material can form a variety of precipitation phases such as fine and dispersed Ge-Nb phase, Ge-Zr phase, Cu-Zr phase, and Cr-rich phase in the matrix through an appropriate preparation process. Multiple precipitated phases work synergistically to pin dislocations and hinder dislocation movement, thereby improving the hardness, strength and high-temperature softening resistance of the material; at the same time, the precipitation of precipitated phase particles can reduce the lattice distortion of the copper matrix, reduce the probability of electron scattering, and improve its conductivity.

[0020] (2) The present invention adopts compression molding technology for the alloy. Compared with cold rolling, compression molding can impose a greater effective strain on the alloy material than cold rolling, and basically does not change the original size of the material. After compression molding, the microstructure of the alloy is refined, and the density of microscopic defects such as dislocations and vacancies is significantly increased, thereby providing more nucleation sites for precipitation phases. In the subsequent aging heat treatment process, more fine and dispersed precipitation phases can be obtained, thereby improving the comprehensive performance of the alloy.

[0021] (3) The present invention adopts staged aging treatment for the alloy after molding. Because a large amount of effective strain is accumulated inside the alloy during the molding process, the internal stress is relatively large. On the one hand, the staged aging treatment can effectively reduce the internal stress of the alloy while maintaining the work hardening state, thereby avoiding the warping deformation of the alloy strip. On the other hand, it is also conducive to the more sufficient precipitation of a large number of fine and dispersed precipitates, which plays a precipitation strengthening effect, thereby improving the strength, hardness and conductivity of the alloy.

[0022] (4) The present invention adopts the process of room temperature rolling + variable temperature aging for the alloy after stage aging. The room temperature rolling of the alloy sample can obtain the required thickness of the finished strip to meet the needs of downstream industries on the one hand; on the other hand, it can introduce strain again to increase the density of microscopic defects such as dislocations and vacancies, form more new precipitation phase nucleation sites, and enable the solute atoms that have not been precipitated during the stage aging process to be fully precipitated during the variable temperature aging process. During the variable temperature aging process, the precipitated phase particles will not grow excessively, resulting in a decrease in their dislocation pinning effect. Therefore, the room temperature rolling combined with the variable temperature aging process can obtain a final sample with good comprehensive performance.

[0023] (5) The copper alloy material of the present invention has excellent comprehensive mechanical properties and electrical conductivity, with a hardness of 200-250 HV, a yield strength of 600-695 MPa, a tensile strength of 625-720 MPa, an elongation after fracture of 6-13%, a softening temperature of 650-730°C, and an electrical conductivity of 80-90% IACS. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the structure of the molding deformation die-groove pressing die (tooth die) of the present invention;

[0025] Figure 2 This is a schematic diagram of the structure of the compression deformation mold-flattening mold of the present invention;

[0026] Figure 3 This is a schematic diagram of a one-time molding deformation of an example of the present invention;

[0027] Figure 4 This is a schematic diagram of two molding deformations of an example of the present invention;

[0028] Figure 5The metallographic structure diagram of the copper alloy material prepared in Example 1;

[0029] Figure 6 This is a transmission electron microscope image of the copper alloy material prepared in Example 1;

[0030] Figure 7 The metallographic structure diagram of the copper alloy material prepared in Comparative Example 1;

[0031] Figure 8 This is a transmission electron microscope image of the copper alloy material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited thereto. The main test methods and standards related to the present invention are as follows: the hardness of the copper alloy material is measured according to GB / T4340.1-2009 "Metallic Material Vickers Hardness Test Part 1: Test Method"; the yield strength, tensile strength and elongation after fracture of the copper alloy material are measured according to GB / T34505-2017 "Copper and Copper Alloy Material Room Temperature Tensile Test Method"; the softening temperature of the copper alloy material is measured according to GB / T33370-2016 "Method for Determining the Softening Temperature of Copper and Copper Alloys"; the conductivity of the copper alloy material is measured according to GB / T351-2019 "Method for Measuring the Resistivity of Metallic Materials", and its value is compared with the International Annealed Copper Standard (100% IACS).

[0033] Example 1

[0034] The mass percentages of the alloy components are: 0.80wt% Cr, 0.10wt% Zr, 0.15wt% Ge, 0.01wt% Nb, and the rest is Cu.

[0035] Its preparation method is:

[0036] (1) Alloy melting and casting: Place the raw materials into the crucible of the induction furnace and evacuate to 3.0×10 -3 Pa, and then 1.1×10 5 Pa of pure argon (Ar volume fraction ≥ 99.99%), smelting is carried out under the protection of pure argon, and the solid is completely melted to form an alloy melt, and then the alloy melt is heated to 1250 ° C, left to stand for 10 minutes, and then cast into a graphite mold, and after cooling, the mold is opened to take out the alloy ingot;

[0037] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 6 hours, and then cooled to room temperature with the furnace;

[0038] (3) Hot rolling: The homogenized alloy material is heated to 750°C and kept at this temperature for 5 minutes, then taken out and quickly hot-rolled into a strip. The total hot-rolling deformation is 80%. The hot-rolled alloy strip is immediately water-quenched and quickly cooled to room temperature.

[0039] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 950°C for 30 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0040] (5) Compression molding: remove the surface oxide scale of the alloy strip after solution treatment, and then perform compression molding at room temperature for 20 times. The groove height and groove width of the upper die groove of the groove die (tooth die) used, and the tooth height and tooth width of the lower die convex teeth are all 7mm; the compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the groove die, and the upper die groove and the lower die convex teeth are engaged with each other, so as to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the groove die, and its placement position is moved by 1 tooth width distance along the lateral direction of the convex teeth relative to the last placement position, and then performing compression molding on the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④;

[0041] (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 200°C at a rate of 10°C / min and kept at this temperature for 60 minutes; then, the temperature is raised to 430°C at a rate of 10°C / min and kept at this temperature for 120 minutes; then, the temperature is lowered to 150°C at a rate of 10°C / min and kept at this temperature for 60 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0042] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 85%;

[0043] (8) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 300°C at a rate of 10°C / min and kept at that temperature for 1 minute; then, the temperature is raised to 430°C at a rate of 10°C / min and kept at that temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample;

[0044] After testing, the obtained copper alloy material has a hardness of 242HV, a yield strength of 685MPa, a tensile strength of 707MPa, an elongation after fracture of about 13%, a softening temperature of 708℃, and a conductivity of 88%IACS.

[0045] Figure 5 The metallographic structure diagram of the copper alloy material prepared in this embodiment is shown in the figure. From the figure, we can see that the grains are fine and uniform, the grain size is about 5-10 μm, and there are fewer coarse grains.

[0046] Figure 6 The transmission electron microscope image of the copper alloy material prepared in this embodiment shows that the precipitated phases have different shapes and sizes, and the precipitated phases are relatively large in number and small in size, and are dispersed in the copper alloy matrix.

[0047] Example 2

[0048] The mass percentages of the alloy components are: 1.20wt% Cr, 0.15wt% Zr, 0.20wt% Ge, 0.01wt% Nb, and the rest is Cu.

[0049] Its preparation method is:

[0050] (1) Alloy melting and casting: Place the raw materials into the crucible of the induction furnace and evacuate to 3.0×10 -3 Pa, and then 1.1×10 5 Pa of pure argon gas (Ar volume fraction ≥ 99.99%), smelting under the protection of pure argon gas (Ar volume fraction ≥ 99.99%), wait until the solid is completely melted to form an alloy melt, then heat the alloy melt to 1340 ° C, let it stand for 10 minutes, and then cast it into a graphite mold, open the mold and take out the alloy ingot after cooling;

[0051] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 980°C for 7 hours, and then cooled to room temperature with the furnace;

[0052] (3) Hot rolling: The homogenized alloy material is heated to 850°C and kept at this temperature for 5 minutes, then taken out and quickly hot-rolled into a strip. The total hot-rolling deformation is 80%. The hot-rolled alloy strip is immediately water-quenched and quickly cooled to room temperature.

[0053] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 1050°C for 45 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0054] (5) Compression molding: remove the surface oxide scale of the alloy strip after solution treatment, and then perform compression molding at room temperature for 12 times. The groove height and groove width of the upper die groove of the groove die (tooth die) used, and the tooth height and tooth width of the lower die convex teeth are all 5mm; the compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the groove die, and the upper die groove and the lower die convex teeth are engaged with each other, so as to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the groove die, and its placement position is moved by 1 tooth width in the transverse direction of the convex teeth relative to the last placement position, and then performing compression molding on the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④;

[0055] (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 250°C at a rate of 5°C / min and kept at this temperature for 60 minutes; then, the temperature is raised to 450°C at a rate of 5°C / min and kept at this temperature for 100 minutes; then, the temperature is lowered to 230°C at a rate of 5°C / min and kept at this temperature for 45 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0056] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 80%;

[0057] (8) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 340°C at a rate of 5°C / min and kept at this temperature for 2 minutes; then, the temperature is raised to 480°C at a rate of 5°C / min and kept at this temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample;

[0058] After testing, the obtained copper alloy material has a hardness of 206HV, a yield strength of 615MPa, a tensile strength of 634MPa, an elongation after fracture of about 10%, a softening temperature of 694℃, and a conductivity of 86%IACS.

[0059] Example 3

[0060] The mass percentages of the alloy components are: 1.00wt% Cr, 0.10wt% Zr, 0.10wt% Ge, 0.04wt% Nb, and the rest is Cu.

[0061] Its preparation method is:

[0062] (1) Alloy melting and casting: Place the raw materials into the crucible of the induction furnace and evacuate to 3.0×10 -3 Pa, and then 1.1×10 5 Pa of pure argon gas (Ar volume fraction ≥ 99.99%), smelting under the protection of pure argon gas (Ar volume fraction ≥ 99.99%), wait until the solid is completely melted to form an alloy melt, then heat the alloy melt to 1220 ° C, let it stand for 10 minutes, and then cast it into a graphite mold. After cooling, open the mold and take out the alloy ingot;

[0063] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 930°C for 5 hours, and then cooled to room temperature with the furnace;

[0064] (3) Hot rolling: The homogenized alloy material is heated to 720°C and kept at this temperature for 8 minutes, then taken out and quickly hot-rolled into a strip. The total hot-rolling deformation is 75%. The hot-rolled alloy strip is immediately water-quenched and quickly cooled to room temperature.

[0065] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 900°C for 30 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0066] (5) Compression molding: remove the surface oxide scale of the alloy strip after solution treatment, and then perform compression molding at room temperature for 16 times. The groove height and groove width of the upper die groove of the groove die (tooth die) used, and the tooth height and tooth width of the lower die convex teeth are all 4mm; the compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the groove die, and the upper die groove and the lower die convex teeth are engaged with each other, so as to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the groove die, and its placement position is moved by 1 tooth width in the transverse direction of the convex teeth relative to the last placement position, and then performing compression molding on the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④;

[0067] (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 200°C at a rate of 10°C / min and kept at this temperature for 60 minutes; then, the temperature is raised to 420°C at a rate of 10°C / min and kept at this temperature for 120 minutes; then, the temperature is lowered to 180°C at a rate of 10°C / min and kept at this temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0068] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 75%;

[0069] (8) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is increased from room temperature to 330°C at a rate of 12°C / min and kept at this temperature for 1.5 minutes; then, the temperature is increased to 420°C at a rate of 12°C / min and kept at this temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample.

[0070] After testing, the obtained copper alloy material has a hardness of 223HV, a yield strength of 643MPa, a tensile strength of 675MPa, an elongation after fracture of about 9%, a softening temperature of 687℃, and a conductivity of 84%IACS.

[0071] Example 4

[0072] The mass percentages of the alloy components are: 0.90wt% Cr, 0.20wt% Zr, 0.25wt% Ge, 0.03wt% Nb, and the rest is Cu.

[0073] Its preparation method is:

[0074] (1) Alloy melting and casting: Place the raw materials into the crucible of the induction furnace and evacuate to 3.0×10 -3 Pa, and then 1.1×10 5 Pa of pure argon gas (Ar volume fraction ≥ 99.99%), smelting is carried out under the protection of pure argon gas (Ar volume fraction ≥ 99.99%), and the solid is completely melted to form an alloy melt, and then the alloy melt is heated to 1280 ° C, left to stand for 10 minutes, and then cast into a graphite mold, and after cooling, the mold is opened to take out the alloy ingot;

[0075] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 950°C for 6 hours, and then cooled to room temperature with the furnace;

[0076] (3) Hot rolling: The homogenized alloy material is heated to 820°C and kept at this temperature for 5 minutes, then taken out and quickly hot-rolled into a strip. The total deformation of hot rolling is 85%. The hot-rolled alloy strip is immediately water quenched and quickly cooled to room temperature.

[0077] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 900°C for 60 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0078] (5) Compression molding: remove the surface oxide scale of the alloy strip after solution treatment, and then perform compression molding at room temperature for 20 times. The groove height and groove width of the upper die groove of the groove die (tooth die) used, and the tooth height and tooth width of the lower die convex teeth are all 8mm; the compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the groove die, and the upper die groove and the lower die convex teeth are engaged with each other, so as to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the groove die, and its placement position is moved by 1 tooth width in the transverse direction of the convex teeth relative to the last placement position, and then performing compression molding on the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④;

[0079] (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 230°C at a rate of 12°C / min and kept at this temperature for 30 minutes; then, the temperature is raised to 430°C at a rate of 12°C / min and kept at this temperature for 90 minutes; then, the temperature is lowered to 150°C at a rate of 12°C / min and kept at this temperature for 45 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0080] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 80%;

[0081] (8) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is increased from room temperature to 320°C at a rate of 15°C / min and kept at that temperature for 1 minute; then, the temperature is increased to 450°C at a rate of 15°C / min and kept at that temperature for 20 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample.

[0082] After testing, the obtained copper alloy material has a hardness of 238HV, a yield strength of 678MPa, a tensile strength of 696MPa, an elongation after fracture of about 12%, a softening temperature of 706℃, and a conductivity of 87%IACS.

[0083] Comparative Example 1

[0084] The mass percentages of the alloy components are: 0.80wt% Cr, 0.10wt% Zr, 0.15wt% Ge, 0.01wt% Nb, and the rest is Cu.

[0085] Its preparation method is:

[0086] (1) Alloy melting and casting: Place the raw materials into the crucible of the induction furnace and evacuate to 3.0×10 -3 Pa, and then 1.1×10 5 Pa of pure argon (Ar volume fraction ≥ 99.99%), smelting is carried out under the protection of pure argon, and the solid is completely melted to form an alloy melt, and then the alloy melt is heated to 1250 ° C, left to stand for 10 minutes, and then cast into a graphite mold, and after cooling, the mold is opened to take out the alloy ingot;

[0087] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C for 6 hours, and then cooled to room temperature with the furnace;

[0088] (3) Hot rolling: The homogenized alloy material is heated to 750°C and kept at this temperature for 5 minutes, then taken out and quickly hot-rolled into a strip. The total hot-rolling deformation is 80%. The hot-rolled alloy strip is immediately water-quenched and quickly cooled to room temperature.

[0089] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 950°C for 30 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0090] (5) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 200°C at a rate of 10°C / min and kept at this temperature for 60 minutes; then, the temperature is raised to 430°C at a rate of 10°C / min and kept at this temperature for 120 minutes; then, the temperature is lowered to 150°C at a rate of 10°C / min and kept at this temperature for 60 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0091] (6) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 85%;

[0092] (7) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is increased from room temperature to 300 °C at a rate of 10 °C / min and kept at this temperature for 1 minute; then, the temperature is increased to 430 °C at a rate of 10 °C / min and kept at this temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample.

[0093] After testing, the obtained copper alloy material has a hardness of 165HV, a yield strength of 497MPa, a tensile strength of 519MPa, an elongation after fracture of about 6%, a softening temperature of 535℃, and a conductivity of 69%IACS.

[0094] This proves that compression molding has a significant effect on the comprehensive properties of the alloy. The mechanical properties and high-temperature softening resistance of the copper alloy material produced without compression molding treatment will be significantly deteriorated, and at the same time, the electrical conductivity will also be significantly reduced.

[0095] Figure 7 This is the metallographic structure diagram of the copper alloy material prepared in this comparative example. From the figure, we can see that its grains are coarse and uneven in size, and the grain size is about 8~40μm.

[0096] Figure 8 The transmission electron microscope image of the copper alloy material prepared in this comparative example shows that the precipitated phase is small in number and large in size.

[0097] Comparative Example 2

[0098] The mass percentages of the alloy components are: 1.30wt% Cr, 0.40wt% Zr, 0.50wt% Ge, 0.10wt% Nb, and the rest is Cu.

[0099] Its preparation method is:

[0100] (1) Alloy melting and casting: Put the raw materials into the crucible of the induction furnace, evacuate to 3.0×10-3Pa, and then introduce 1.1×105Pa of pure argon gas (Ar volume fraction ≥99.99%). Smelt under the protection of pure argon gas (Ar volume fraction ≥99.99%) until the solid is completely melted to form alloy melt. Then, heat the alloy melt to 1340℃, let it stand for 10 minutes, and then cast it into a graphite mold. After cooling, open the mold and take out the alloy ingot;

[0101] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 980°C for 7 hours, and then cooled to room temperature with the furnace;

[0102] (3) Hot rolling: The homogenized alloy material is heated to 850°C and kept at this temperature for 5 minutes, then taken out and quickly hot-rolled into a strip. The total hot-rolling deformation is 80%. The hot-rolled alloy strip is immediately water-quenched and quickly cooled to room temperature.

[0103] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a solution temperature of 1050°C for 45 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0104] (5) Compression molding: remove the surface oxide scale of the alloy strip after solution treatment, and then perform compression molding at room temperature for 12 times. The groove height and groove width of the upper die groove of the groove die (tooth die) used, and the tooth height and tooth width of the lower die convex teeth are all 5mm; the compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the groove die, and the upper die groove and the lower die convex teeth are engaged with each other, so as to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the groove die, and its placement position is moved by 1 tooth width in the transverse direction of the convex teeth relative to the last placement position, and then performing compression molding on the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④;

[0105] (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 250°C at a rate of 5°C / min and kept at this temperature for 60 minutes; then, the temperature is raised to 450°C at a rate of 5°C / min and kept at this temperature for 100 minutes; then, the temperature is lowered to 230°C at a rate of 5°C / min and kept at this temperature for 45 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0106] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 80%;

[0107] (8) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 340°C at a rate of 5°C / min and kept at this temperature for 2 minutes; then, the temperature is raised to 480°C at a rate of 5°C / min and kept at this temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample;

[0108] After testing, the obtained copper alloy material has a hardness of 192HV, a yield strength of 571MPa, a tensile strength of 590MPa, an elongation after fracture of about 3%, a softening temperature of 600℃, and a conductivity of 71%IACS.

[0109] That is to say, it is proved that when the content of Cr, Zr, Ge and Nb elements in the alloy composition is higher than the specified range, the mechanical properties and high temperature softening resistance of the copper alloy material obtained will be significantly deteriorated, and at the same time, the electrical conductivity will also be significantly reduced.

[0110] Comparative Example 3

[0111] The mass percentages of the alloy components are: 0.70wt% Cr, 0.05wt% Zr, 0.05wt% Ge, 0.005wt% Nb, and the rest is Cu.

[0112] Its preparation method is:

[0113] (1) Alloy melting and casting: Place the raw materials into the crucible of the induction furnace and evacuate to 3.0×10 -3 Pa, and then 1.1×10 5 Pa of pure argon gas (Ar volume fraction ≥ 99.99%), smelting under the protection of pure argon gas (Ar volume fraction ≥ 99.99%), wait until the solid is completely melted to form an alloy melt, then heat the alloy melt to 1220 ° C, let it stand for 10 minutes, and then cast it into a graphite mold. After cooling, open the mold and take out the alloy ingot;

[0114] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 930°C for 5 hours, and then cooled to room temperature with the furnace;

[0115] (3) Hot rolling: The homogenized alloy material is heated to 720°C and kept at this temperature for 8 minutes, then taken out and quickly hot-rolled into a strip. The total hot-rolling deformation is 75%. The hot-rolled alloy strip is immediately water-quenched and quickly cooled to room temperature.

[0116] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 900°C for 30 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0117] (5) Compression molding: remove the surface oxide scale of the alloy strip after solution treatment, and then perform compression molding at room temperature for 16 times. The groove height and groove width of the upper die groove of the groove die (tooth die) used, and the tooth height and tooth width of the lower die convex teeth are all 4mm; the compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the groove die, and the upper die groove and the lower die convex teeth are engaged with each other, so as to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the groove die, and its placement position is moved by 1 tooth width in the transverse direction of the convex teeth relative to the last placement position, and then performing compression molding on the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④;

[0118] (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 200°C at a rate of 10°C / min and kept at this temperature for 60 minutes; then, the temperature is raised to 420°C at a rate of 10°C / min and kept at this temperature for 120 minutes; then, the temperature is lowered to 180°C at a rate of 10°C / min and kept at this temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling.

[0119] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 75%;

[0120] (8) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is increased from room temperature to 330°C at a rate of 12°C / min and kept at this temperature for 1.5 minutes; then, the temperature is increased to 420°C at a rate of 12°C / min and kept at this temperature for 30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample.

[0121] After testing, the obtained copper alloy material has a hardness of 155HV, a yield strength of 466MPa, a tensile strength of 487MPa, an elongation after fracture of about 4%, a softening temperature of 554℃, and a conductivity of 75%IACS.

[0122] That is to say, it is proved that when the content of Cr, Zr, Ge and Nb elements in the alloy composition is lower than the specified range, the mechanical properties and high temperature softening resistance of the copper alloy material obtained will be significantly deteriorated, and at the same time, the electrical conductivity will also be significantly reduced.

[0123] Comparative Example 4

[0124] The mass percentages of the alloy components are: 0.90wt% Cr, 0.20wt% Zr, 0.25wt% Ge, 0.03wt% Nb, and the rest is Cu.

[0125] Its preparation method is:

[0126] (1) Alloy melting and casting: Place the raw materials into the crucible of the induction furnace and evacuate to 3.0×10 -3 Pa, and then 1.1×10 5 Pa of pure argon gas (Ar volume fraction ≥ 99.99%), smelting is carried out under the protection of pure argon gas (Ar volume fraction ≥ 99.99%), and the solid is completely melted to form an alloy melt, and then the alloy melt is heated to 1280 ° C, left to stand for 10 minutes, and then cast into a graphite mold, and after cooling, the mold is opened to take out the alloy ingot;

[0127] (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 950°C for 6 hours, and then cooled to room temperature with the furnace;

[0128] (3) Hot rolling: The homogenized alloy material is heated to 820°C and kept at this temperature for 5 minutes, then taken out and quickly hot-rolled into a strip. The total deformation of hot rolling is 85%. The hot-rolled alloy strip is immediately water quenched and quickly cooled to room temperature.

[0129] (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 900°C for 60 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0130] (5) Compression molding: remove the surface oxide scale of the alloy strip after solution treatment, and then perform compression molding at room temperature for 20 times. The groove height and groove width of the upper die groove of the groove die (tooth die) used, and the tooth height and tooth width of the lower die convex teeth are all 8mm; the compression molding steps include: ① placing the alloy strip after removing the surface oxide scale in the middle of the groove die, and the upper die groove and the lower die convex teeth are engaged with each other, so as to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip: ③ placing the alloy strip in the middle of the groove die, and its placement position is moved by 1 tooth width in the transverse direction of the convex teeth relative to the last placement position, and then performing compression molding on the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally (clockwise or counterclockwise) by 90°, and repeating steps ①②③④;

[0131] (6) Constant temperature aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to constant temperature aging under the protection of pure argon gas. The aging temperature is 460°C and the holding time is 2 hours. Subsequently, the alloy strip is immediately subjected to water quenching treatment and rapidly cooled to room temperature.

[0132] (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 80%;

[0133] (8) Constant temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to constant temperature aging treatment under the protection of pure argon gas. The aging temperature is 450°C and the holding time is 2 hours. The alloy strip is then immediately water quenched and rapidly cooled to room temperature.

[0134] After testing, the obtained copper alloy material has a hardness of 179HV, a yield strength of 540MPa, a tensile strength of 559MPa, an elongation after fracture of about 6%, a softening temperature of 582°C, and a conductivity of 77%IACS.

[0135] That is to say, it is proved that when the stage aging and variable temperature aging are changed to constant temperature aging, the mechanical properties and high temperature softening resistance of the copper alloy material obtained will be significantly deteriorated, and at the same time, the electrical conductivity will also be significantly reduced.

[0136] The above embodiments and comparative examples are only preferred examples of the present invention, and the specific implementation methods of the present invention cannot be considered to be limited thereto. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a Cu-Cr-Zr alloy for a high current electrical connector, characterized in that: The Cu-Cr-Zr alloy contains the following components, calculated based on the sum of mass percentages being 100%, respectively: 0.80-1.20wt% Cr, 0.10-0.30wt% Zr, 0.10-0.30wt% Ge, 0.01-0.06wt% Nb, and the remainder being Cu; the sum of mass percentages of Cr+Zr is 0.90-1.50wt%, and the sum of mass percentages of Ge+Nb is 0.11-0.36wt%; The method for preparing the Cu-Cr-Zr alloy for high current electrical connectors comprises the following steps: (1) Alloy melting and casting: Under the protection of pure argon, the raw materials are placed in an induction furnace for melting, and then the resulting alloy melt is heated to above 1200°C, allowed to stand for 10 minutes, and then cast into a mold and cooled to room temperature to obtain an alloy ingot; (2) Homogenization treatment: Under the protection of pure argon, the obtained ingot is placed in a heat treatment furnace for homogenization treatment at a temperature of 900°C to 980°C for 5 to 8 hours, and then cooled to room temperature with the furnace; (3) Hot rolling: The homogenized alloy material is placed in a heat treatment furnace, heated to 700°C~850°C, kept warm for 5~10 minutes, then taken out and quickly hot-rolled into strips. The total hot rolling deformation is 60%~85%. The hot-rolled alloy strips are immediately water quenched and quickly cooled to room temperature. (4) Solution treatment: Under the protection of pure argon, the hot-rolled alloy strip is placed in a heat treatment furnace for solution treatment at a temperature of 900°C to 1050°C for 30 to 60 minutes. The alloy strip is then immediately water quenched and rapidly cooled to room temperature. (5) Compression molding: remove the surface oxide scale of the alloy strip after solid solution treatment, and then perform compression molding at room temperature for 8 to 20 times; the compression molding die includes a groove die and a flattening die, the upper die of the groove die is provided with a groove, and the lower die is provided with a convex tooth, the convex tooth and the groove are engaged with each other, the groove height and groove width of the upper die groove and the tooth height and tooth width of the lower die convex tooth are equal, which is 3 to 10 mm, and both are distributed at equal intervals; (6) Stage aging treatment: The alloy strip after mold deformation is placed in a heat treatment furnace and subjected to stage aging under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 200-250°C at a rate of 5-15°C / min and kept at this temperature for 30-60 minutes; then, the temperature is raised to 400-460°C at a rate of 5-15°C / min and kept at this temperature for 90-120 minutes; then, the temperature is lowered to 150-250°C at a rate of 5-15°C / min and kept at this temperature for 30-60 minutes; finally, the alloy strip is cooled to room temperature by air cooling. (7) Room temperature rolling: The alloy strip after stage aging treatment is rolled at room temperature, and the total rolling deformation is 50%~90%; (8) Temperature aging treatment: The alloy strip after room temperature rolling is placed in a heat treatment furnace and subjected to temperature aging treatment under the protection of pure argon. The aging process is as follows: first, the temperature is raised from room temperature to 300-350°C at a rate of 5-15°C / min and kept at this temperature for 1-2 minutes; then, the temperature is raised to 400-500°C at a rate of 5-15°C / min and kept at this temperature for 15-30 minutes; finally, the alloy strip is cooled to room temperature by air cooling to obtain the final sample; The specific operation steps of the compression molding include: ① placing the alloy strip after removing the surface oxide scale in the middle of the slot die, and interlocking the upper die groove and the lower die convex teeth with each other to perform compression molding on the alloy strip; ② using a flattening die to flatten the deformed alloy strip; ③ placing the alloy strip in the middle of the slot die, and its placement position is moved by an odd number of tooth widths along the lateral direction of the convex teeth relative to the last placement position, and then compression molding the alloy strip to deform the undeformed parts of the alloy strip; ④ using a flattening die to flatten the deformed alloy strip; ⑤ rotating the alloy strip horizontally by 90°, and repeating steps ①②③④.

2. The preparation method according to claim 1, characterized in that: The raw materials used are pure copper blocks with a purity of ≥99.9wt%, containing 5-10wt% of Cu-Cr master alloy, 40-60wt% of Cu-Zr master alloy, 10%-20wt% of Cu-Ge master alloy, and 0.5-1.0wt% of Cu-Nb master alloy.

3. The preparation method according to claim 1, characterized in that: The volume fraction of Ar in the pure argon gas used is ≥99.99%.

Citation Information

Patent Citations

  • A method for preparing high-performance copper alloy

    CN109266877B

  • Copper alloy material for 5G base station power connector and preparation method thereof

    CN113943874A

  • Copper alloy commonly having conductivity and strength

    JP1995054079A